Analysis of The Quality of Physiotherapy Services For BPJS Patients In Hospitals On The Island of Java - Lasmi, Asifa; Mustika Rehalat, Syani; Putri, Laela; Nur Alpiah, Dini (International Journal of Social Research, 2024)
The growing emphasis on patient-centered healthcare highlights the critical need for high-quality services that meet patient satisfaction, particularly in physiotherapy clinics. This study aims to explore the relationship between the quality of physiotherapy services and patient satisfaction, focusing on various dimensions such as tangibility, reliability, responsiveness, assurance, and empathy. A literature review was conducted, analyzing studies from 2013 to 2023 to assess the effectiveness of physiotherapy services in different settings. The findings indicate a significant correlation between service quality and patient satisfaction, with a substantial number of patients reporting satisfaction with the services received. However, certain areas, such as communication and facility conditions, were identified as needing improvement. The study underscores the importance of enhancing service quality to meet patient expectations and improve overall healthcare outcomes. The results are expected to contribute to the development of more effective physiotherapy services and serve as a reference for future research in this area.